TECHNICAL TRADING RULES AND TRADING SIGNALS IN THE BLACK MARKET FOR FOREIGN EXCHANGE IN SUDAN - ONOUR, Ibrahim A. (Theoretical and Practical Research in Economic Fields; Vol 9 No 1 (2018): TPREF, Volume IX, Issue 1(17), Summer 2018, 2018)
This paper aims to assess the level of departure of the actual black-market rate from its real level. Our finding indicates divergence of the actual black-market rate from the real level, ranging from 7% in October 2016 to about 38% in November 2017. This result implies 38% of the foreign exchange price in the black-market rate in November 2017 was due to manipulative trading strategies exerted by a few powerful traders in the market. The study concludes that in the very short term to curb increasing depreciation of the domestic currency rate in the black market, it is essential to control domestic liquidity expansion, and raise the cost (risk) of dealing in the black market by imposing higher penalty cost on dealers in this market.